A novel approach to recoil pad enhancement in rifles via topological design with material extrusion and SLA - Alshihabi, Mamoun; Bilge, Tülin; Kayacan, Mevlüt Yunus; Farooq, Muhammad Umar; Ali, Shafahat (Frontiers in Mechanical Engineering, 2025)
Excessive recoil in firearms reduces shooting accuracy, causes user discomfort, and increases mechanical wear over time. This creates a need for effective solutions that can improve recoil management. This study investigates the use of advanced lattice structures made from thermoplastic polyurethane (TPU) and resin to enhance vibration damping and impact absorption in firearm components. Four lattice geometries were used, including Voronoi, Weaire Phelan, Gyroid, and Kelvin Cell. These structures were fabricated using two additive manufacturing methods. Material extrusion was applied for TPU parts to provide flexibility and strength, while Stereolithography (SLA), a light-based resin curing technique, was used to produce intricate resin structures. These approaches highlight the adaptability of additive manufacturing in producing functional parts that offer both vibration control and impact resistance. The performance of each structure was evaluated through vibration damping in two modes, rapid impact testing, and compression strength assessments. TPU samples consistently outperformed resin in both damping and energy absorption. Voronoi TPU exhibited the highest damping ratio, improving by 331 percent in the first mode with a value of 1.25 and by 300 percent in the second mode with a value of 0.20 compared to the original solid part. Weaire Phelan TPU reached the highest impact energy absorption at 6.45 joules, which is an improvement of 18.14 percent. Gyroid TPU absorbed energy the fastest, reaching a peak of 5.4 joules in only 14 milliseconds. This study introduces a new design approach by applying lattice structures to recoil pads, enabling enhanced performance and a high degree of customization.